The Work of Managers - Tengblad, Stefan (Ascent Audio, 2019)
Managers are significant actors in contemporary organizations and yet there is very little deep-level analysis of what managers do, and how they understand their managerial selves and social situations. Instead of evaluating management techniques according to their internal logic and systematic qualities, this book advances the "practice perspective," using behavior and activities of successful, experienced, and skilled managers as the primary data for theorizing good management. In this book, academics review classic literature on managerial work, discuss methodological and theoretical approaches, and present empirical studies on various kinds of managers at different levels of organizations, in different roles, and different sectors, from construction site managers and CEOs of large companies to university vice chancellors and front-line health care managers. It makes the case for studies of managerial work that look beyond the rational and ordered world to the challenges presented by, inter alia, work and information overload, complexity, performance pressures, unintended consequences, and irreconcilable expectations.